Parents' Role in Fostering Islamic Culture at SD Muhammadiyah 2 - Fahruddin, Fahruddin; Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2024)
Background: The need for character education in Indonesian schools underscores the importance of integrating Islamic values into the educational framework. Specific Background: This study examines parental involvement in fostering an Islamic culture at SD Muhammadiyah 2 Tulangan, highlighting challenges in parents' understanding and engagement with Islamic values. Knowledge Gap: There is limited research on the effectiveness of parental participation in promoting Islamic values in schools, despite existing policies. Aims: The research aims to assess parental synergy's role in building an Islamic culture and identify strategies for enhancing collaboration between parents and educators. Results: Findings reveal significant gaps in parents’ understanding and involvement, exacerbated by technological influences and differing interpretations of Islamic teachings. Novelty: The study proposes a framework to strengthen parental engagement through communication, workshops, and collaborative activities. Implications: The results emphasize the need for an integrated approach that involves both parents and teachers to foster a strong Islamic educational environment, ultimately developing students with robust character and essential life skills. Highlights : Parental Engagement: Essential for fostering an Islamic culture in schools. Understanding Gaps: Parents often lack knowledge of Islamic values and their importance. Collaborative Strategies: Effective communication and workshops can enhance synergy between parents and educators. Keywords: Islamic education, parental involvement, character development, educational framework, SD Muhammadiyah 2 Tulangan